Penerapan pembelajaran model kooperatif yang mengoptimalkan kecerdasan majemuk untuk meningkatkan prestasi belajar trigonometri pada mahasiswa universitas muhammadiyah bone - Andi Trisnowali MS; Andi Cahaya Rezky Andini; Ahmad Talib (FKIP Universitas Mataram, 2026)
This study aims to determine the improvement of students’ learning achievement and to examine their responses toward the implementation of a cooperative learning model based on interpersonal and logical-mathematical intelligences in the Trigonometry course. This research employed a quantitative approach with a one-group pretest–posttest design. The subjects consisted of 19 students who were taught using the cooperative learning model over several meetings. Data were collected through achievement tests, student response questionnaires, and learning implementation observation sheets. The results showed that the students’ average achievement score increased from 68.42 to 85.26, with the Wilcoxon Signed Rank Test (Z = -3.922; p < 0.000) indicating a significant difference between the pretest and posttest scores. The N-Gain value of 0.533 fell into the moderate category, indicating that the cooperative learning model was quite effective in improving student achievement. Furthermore, the average student response (85) and learning implementation score (89.47) were both in the very high category, suggesting a positive attitude toward the learning model. Therefore, the implementation of a cooperative learning model based on interpersonal and logical-mathematical intelligences was proven effective in improving student achievement and active engagement in learning Trigonometry.